Long-life proton exchange membrane with bipyridine side group and preparation method of long-life proton exchange membrane
By introducing bipyridine pendant structure into perfluoroion polymers, capturing or quenching free radicals, the problem of low chemical stability of the proton exchange membrane is solved, and a proton exchange membrane with high chemical stability and long life is achieved to meet the fuel Efficient operation requirements of batteries.
Patent Information
- Application Number
- CN202411160244.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-27
- Filing Date
- 2021-11-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing perfluorosulfonic acid proton exchange membrane has low chemical stability, resulting in a short service life of fuel cells, and the existing methods fail to effectively capture or quench free radicals during polymer synthesis, resulting in chemical degradation of the membrane.
The perfluoroion polymer with bipyridine pendant groups was used, and the functional bipyridine structural units were introduced into the structure to capture or quench free radicals, and the synthesis was highly chemically stable by one-step grafting reaction and ion exchange treatment. and mechanically strong proton exchange membrane.
It significantly improves the chemical stability and service life of the proton exchange membrane, extends the life of the polymer, and meets the requirements of high ion exchange capacity and conductivity without reducing mechanical strength and thermal stability.
Smart Images

Figure CN119264301A_ABST
Abstract
Description
[0001] This application is a divisional application of the application numbered 202111299572.0, and the invention name is a class of perfluoroionic polymers with bipyridine side groups and synthesis methods and applications Technical Field
[0002] The invention belongs to the technical field of fluorine-containing polymer materials and relates to a long-life proton exchange membrane with bipyridine side groups and a preparation method thereof. Background Art
[0003] Proton exchange membrane fuel cell is an electrochemical device with high energy conversion efficiency. It is environmentally friendly. The only product in the energy conversion process is water (the overall reaction equation can be summarized as 2H2+O2=2H2O), which can avoid environmental pollution. It is an efficient and environmentally friendly energy conversion device. Proton exchange membrane (PEM) is the core component of proton exchange membrane fuel cell (PEMFC). It acts as an isolation membrane to separate fuel and oxidant to prevent them from reacting directly, and also acts as an electrolyte to conduct protons.
[0004] The most widely used proton exchange membrane at present is the perfluorosulfonic acid proton membrane, whose molecular structure includes a perfluoro main chain skeleton -(CF2CF2)m-(CF2CF)n-, and a perfluoroether structure with a sulfonic acid group (-SO3H) as the end group of the side chain. As the key material of these clean energy technologies, in addition to having high ionic conductivity, electrochemical stability is also a factor that must be considered. Because the stability of the proton exchange membrane directly determines the long-term operation life of the fuel cell. However, during the operation of the fuel cell, hydroxyl radicals (·OH) will inevitably be produced as a byproduct. These ·OH will react with the sulfonic acid group and eventually lead to chemical degradation of the proton membrane. Therefore, improving the chemical stability of the proton membrane is of great significance to extending the service life of the fuel cell.
[0005] Current research suggests that the chemically stable degradation process of PFSIs is mainly a "zipper-like" degradation of the main chain or side chain of the polymer membrane attacked by free radicals (HO·&HOO·), which ultimately leads to the overall degradation of the polymer. During the synthesis of perfluoropolymers, initiators will inevitably produce unstable groups such as -CF=CF2, -COOH, -CF2SO3H and -CF2H at the ends of the molecular chains, and chemical degradation often occurs at the ends of these non-completely fluorinated molecular chains with unstable groups. Hydroxyl radicals will attack these groups, leading to degradation reactions. At present, there are two main means to improve the chemical stability of polymers due to free radical attack:
[0006] (1) Inhibit the generation of free radicals during polymer application.
[0007] (2) Quench or capture the generated free radicals by optimizing the polymer structure.
[0008] Ramani et al. [The Journal of Physical Chemistry B, 2007, 111 (30), 8684-8690] added cerium oxide to the ion membrane to capture the free radicals in the system, thereby alleviating the attack on the ion membrane and increasing the chemical stability of the membrane. The results show that the ion membrane with the addition of cerium oxide has good chemical stability. Chinese patent document CN102479956A (CN201010566820.9) improves the chemical stability of the membrane by modifying the microscopic morphology of the proton exchange membrane. In addition, the effect of scavenging free radicals is achieved by adding small molecule additives such as phenol and hindered amine to the membrane. Although the above technology can partially solve the problem of free radical tolerance of the membrane, the above method first prepares the polymer into an ion membrane, and then adopts a post-treatment strategy for the ion membrane to resist the attack of free radicals, and does not take measures to quench or capture the generated free radicals at the source of the polymer and its synthesis process. The shortcomings of this type of method mainly include: 1) This type of method will cause the small molecule additives to be unevenly distributed in the membrane and easily aggregate. 2) Such added substances do not contain ionic groups, which will reduce the strength and conductivity of the membrane. 3) Small molecule additives will continue to degrade and lose during long-term use and cannot provide long-term protection. Summary of the invention
[0009] The invention aims to solve the problem that the existing perfluorosulfonic acid resin has low chemical stability, resulting in a short service life of the perfluorosulfonic acid proton membrane, and provides a class of perfluoroionic polymers with bipyridine side groups, and a synthesis method and application thereof.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] A class of perfluoroionic polymers (PFSIs) with bipyridine side groups, the structural unit of the polymer is shown in formula (I):
[0012]
[0013] Wherein, the structure of formula (I) comprises an A unit and a B unit: the A unit is a bipyridine structural unit, which comprises a bipyridine group M and a perfluoroether structural unit, and the B unit comprises an ionic group -SO3H and a perfluoroether structural unit;
[0014] In the structure of formula (I), m is an integer of 0-5, and n is an integer of 1-6; preferably, m is an integer of 1-3, and n is an integer of 1-3;
[0015] Further preferably, m is 1 and n is 2;
[0016] In the structure of formula (I), x is an integer of 1 to 30, x+y / (x+y+z)=0.10 to 0.80, y / (y+z)=0.20 to 0.70, and y / (y+z) is defined as the grafting rate;
[0017] Preferably x+y / (x+y+z)=0.20-0.40, y / (y+z)=0.20-0.40;
[0018] More preferably, y / y+z=0.26-0.35;
[0019] The structure of the monomer reagent providing the bipyridine reagent M in the polymer A unit is shown in Formula II:
[0020]
[0021] At least one of the R1 to R8 groups contains -NH2, and the other groups are electron-withdrawing groups or electron-donating groups, and the other groups cannot be electron-withdrawing groups at the same time, and the number of electron-withdrawing groups is at most 3.
[0022] Preferably, the R1 to R8 groups are -NH2, -CH2NH2, -Ph (Ph represents a benzene ring), -PhNH2, -PhCOOH, -Cl, -O-CH3, -CH3, -H, -F, -Br, CH3CH2-, (CH3)2CH-, or (CH3)3C-.
[0023] Among them, the electron donating groups in the above groups include: -NH2, -CH2NH2, -Ph, -PhNH2, -PhCOOH, -O-CH3, -CH3, CH3CH2-, (CH3)2CH-, (CH3)3C-; the electron withdrawing groups include -F, -Br, -Cl; the electron withdrawing ability of the above electron withdrawing groups is ranked as follows: (-F>-Cl>-Br).
[0024] In the present invention, the electron-donating group is conducive to forming a conjugated system with the bipyridine ring, and can combine with free radicals to extend the life of the perfluoro ion polymer. The position of each group has no effect on the grafting rate of the M group.
[0025] Preferably, the R1 to R5 are not all -NH2 at the same time; the number of -NH2 in R1 to R5 is at most 3.
[0026] Preferably, R1 is -H, -Br, -Cl, -O-CH3 or -CH3; R2 is -H, -NH2, -Cl or -CH3; R3 is -H, -Br, -Ph (Ph represents a benzene ring) or -CH3; R4 is -H, -Br, -Cl, -Ph or -CH3; R5 is -H, -Br, -NH2 or -CH3; R6 is -H, -Br, -Cl, -O-CH3 or -CH3; R7 is -H, -Br, -NH2, -NO2 or -CH3; R8 is -H, -Br, -NH2 or -CH3.
[0027] Further preferably, R1 is -H, -Br or -CH3; R2 is -NH2 or -CH3; R3 is -H, -Ph or -CH3; R4 is -H, -Ph or -CH3; R5 is -NH2 or -CH3; R6 is -H, -Br or -CH3; R7 is -H, -NH2 or -NO2; R8 is -H, -NH2 or -CH3.
[0028] In at least one preferred technical solution of the present invention, R8 is -NH2, and R1, R2, R3, R4, R5, R6, and R7 are H.
[0029] In at least one preferred technical solution of the present invention, R1 is -NH2, and R2, R3, R4, R5, R6, R7, and R8 are H.
[0030] In at least one preferred technical solution of the present invention, R2 is -NH2, and R1, R3, R4, R5, R6, R7, and R8 are H.
[0031] According to the present invention, the number average molecular weight of the PFSIs of formula (I) is 200,000 to 1,000,000, preferably 200,000 to 600,000, and particularly preferably 300,000 to 500,000.
[0032] The polymer of the present invention has the following advantages: (1) retaining the ultra-stable advantageous unit of the perfluoropolymer - (CF2CF2) x -, ensuring sufficient mechanical strength and thermal stability of the polymer. (2) Chemical grafting is performed on the terminal groups of the side chains of the perfluorosulfonyl fluoride resin, and the introduced functional bipyridine structural units can effectively capture or quench free radicals, thereby weakening or slowing down the degradation of the polymer. (3) The perfluoroion polymer synthesized by the present invention can simultaneously meet the requirements of high IEC and strong chemical stability, and has a wide range of applications. By adjusting the proportion of bipyridine structural units, i.e., the grafting rate, perfluoroion polymers (PFSIs) that meet various requirements of IEC and chemical stability can be synthesized.
[0033] Another object of the present invention is to provide a method for synthesizing a class of perfluoroionic polymers (PFSIs) with bipyridine side groups, comprising the following steps:
[0034] (1) a perfluorosulfonyl fluoride resin (Formula III) is subjected to a one-step grafting reaction with a monomer reagent providing a bipyridine group M in an organic solvent to synthesize an intermediate product with a bipyridine side group (Formula IV);
[0035] The reaction process is shown in formula (1-1):
[0036]
[0037] (2) The intermediate product obtained in step (1) is treated with alkali and acid to complete ion exchange, and the unreacted sulfonyl fluoride group (-SO2F) is converted into a sulfonic acid group (-SO3H). After washing and drying, a perfluoroionic polymer with a bipyridine side group (Formula I) is obtained. The reaction process is shown in Formula (1-2):
[0038]
[0039] Preferably, the organic solvent in step (1) is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, dimethyl sulfoxide or ethyl acetate.
[0040] Preferably, in step (1), the molar ratio of the monomer reagent providing the pyridine group M to the perfluorosulfonyl fluoride resin (Formula III) is greater than 3, more preferably 5 to 8:1.
[0041] Preferably, the mass volume ratio of the perfluorosulfonyl fluoride resin to the organic solvent in step (1) is 1:1 to 10, g / mL; more preferably 1:1 to 5, g / mL; most preferably 1:1 to 3, g / mL.
[0042] Preferably, the reaction temperature in step (1) is 15 to 150° C., preferably 50 to 100° C., and the reaction time is 1 to 48 hours, preferably 20 to 24 hours.
[0043] Preferably, the one-step grafting reaction of step (1) is: first dissolving the monomer reagent in an organic solvent, then adding perfluorosulfonyl fluoride resin for grafting reaction to synthesize an intermediate product with bipyridine side groups, or first pre-swelling the perfluorosulfonyl fluoride resin in an organic solvent, and then adding the monomer reagent.
[0044] Further preferably, the pre-swelling in step (1) is: pre-swelling the perfluorosulfonyl fluoride resin in an organic solvent at 40 to 80° C. for 60 to 100 minutes.
[0045] Further preferably, the grafting reaction in step (1) is as follows: placing an organic solvent in a container, adding a monomer reagent under stirring and nitrogen protection, slowly heating until the monomer reagent is completely dissolved, and then adding a perfluorosulfonyl fluoride resin to react.
[0046] Preferably, the base in step (2) is one of sodium hydroxide and potassium hydroxide, with a concentration of 5 to 50 wt%, preferably 15 to 40 wt% of sodium hydroxide; the acid in step (2) is one of hydrochloric acid, sulfuric acid and nitric acid, with a concentration of 5 to 50 wt%, preferably 25 to 40 wt% of sulfuric acid or nitric acid.
[0047] Preferably, the washing in step (2) is performed by washing with deionized water multiple times, the drying temperature is 55 to 65° C., and the drying time is 18 to 36 hours.
[0048] The ion exchange capacity of the above-mentioned perfluoro ion polymer with bipyridine side groups (Formula I) and the proportion of bipyridine structural units can be determined by acid-base titration. The proportion of bipyridine structural units can be controlled by adjusting the amount of monomer reagent added, reaction time and reaction temperature in step (1), that is, the grafting rate of the reaction is controlled, and then the ion exchange capacity of the perfluoro ion polymer is controlled.
[0049] The above-mentioned perfluoroionic polymer with bipyridine side groups can be used in one or more of the following applications: 1) in the manufacture of ion exchange membranes in fuel cells or electrolysis devices; 2) as a superacid in chemical catalysis; 3) in electrodialysis; 4) in seawater desalination; 5) in gas separation; 6) in the preparation of membrane electrodes for fuel cells; 7) in sewage treatment.
[0050] The present invention also provides a long-life proton exchange membrane, wherein the proton membrane component comprises the above-mentioned perfluoro ion polymer with bipyridine side groups (Formula I).
[0051] A proton exchange membrane for a fuel cell, wherein the structure of the proton exchange membrane is selected from one of the following:
[0052] 1) A proton exchange membrane prepared from the above-mentioned perfluoro ion polymer with bipyridine side groups;
[0053] 2) A proton exchange membrane prepared from a mixture of the above-mentioned perfluoro ionic polymer with bipyridine side groups and a perfluorosulfonic acid polymer.
[0054] The above-mentioned preparation methods include spin coating, screen printing, dip coating, inkjet printing, solution casting and spray pyrolysis, etc., and the solution casting method is preferred.
[0055] Preferably, according to the present invention, the ion exchange capacity of the proton exchange membrane is 0.9-1.5 mmol / g, the ion conductivity is 50-200 mS / cm, the thermal degradation temperature is 300-325°C, and after 200 hours of Fenton test, the ion exchange capacity retention rate and the ion conductivity retention rate are both above 93%. Preferably, the ion conductivity of the proton exchange membrane is 80-90 mS / cm. Preferably, the thickness of the proton exchange membrane is 10-200 μm.
[0056] The long-life proton exchange membrane includes a membrane prepared entirely using the above-mentioned perfluoro ion polymer with bipyridine side groups and a composite membrane prepared by adding the above-mentioned perfluoro ion polymer with bipyridine side groups as a free radical quencher into a conventional perfluorosulfonic acid polymer.
[0057] The present invention also provides a method for preparing the long-life proton exchange membrane, wherein the perfluoro ion polymer (Formula I) with bipyridine side groups is dissolved in an organic solvent to obtain a perfluoro ion polymer solution, and then a solution casting method is used to directly prepare a perfluorosulfonic acid proton exchange membrane;
[0058] Alternatively, the above-mentioned perfluoro ion polymer with bipyridine side groups (Formula I) is added as a free radical quencher into a conventional perfluorosulfonic acid resin solution to obtain a perfluoro ion polymer composite solution, and a composite proton membrane is prepared by a solution casting method.
[0059] Preferably, the mass fraction of the perfluoro ion polymer solution is 5 to 35 wt %, more preferably 10 to 25 wt %.
[0060] Preferably, the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, ethanol / water mixed solvent, isopropanol / water mixed solvent, dimethyl sulfoxide or ethyl acetate.
[0061] Further preferably, the volume ratio of ethanol to water in the ethanol / water mixed solvent is 8-9:1-2; the volume ratio of isopropanol to water in the isopropanol / water mixed solvent is 8-9:1-2.
[0062] Preferably, the mass proportion of the perfluoro ion polymer with bipyridine side groups in the composite proton membrane is greater than or equal to 5%, and more preferably greater than or equal to 10%.
[0063] Preferably, the mass fraction of the perfluoro ion polymer composite solution is 5 to 30 wt %.
[0064] Preferably, according to the present invention, the steps of the solution casting method are: coating the perfluoro ion polymer solution or the perfluoro ion polymer composite solution on a quartz watch glass, pre-drying at 80-90°C, drying at 140-150°C for 90-100 minutes, and removing from the mold.
[0065] In the present invention, when preparing the composite proton exchange membrane, the ionic conductivity and chemical stability of the proton exchange membrane can be regulated by adjusting the proportion of the perfluoroionic polymer according to the requirements of product performance, thereby regulating the service life of the proton exchange membrane.
[0066] The present invention also provides a long-life membrane electrode for a free radical resistant fuel cell, wherein the catalyst mixture component of the catalyst layer of the membrane electrode comprises the above-mentioned perfluoro ion polymer with bipyridine side groups.
[0067] A membrane electrode for an anti-free radical fuel cell consists of an electrode layer and a proton exchange membrane. The electrode layer includes a gas diffusion layer and a catalyst layer. The electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode. The proton exchange membrane is located between the hydrogen electrode and the oxygen electrode.
[0068] The proton exchange membrane may be the long-life proton exchange membrane of the present invention or other conventional proton exchange membranes for fuel cells.
[0069] The method for preparing the long-life membrane electrode for the above-mentioned free radical resistant fuel cell comprises the following steps:
[0070] (1) dissolving the above-mentioned perfluoro ion polymer with bipyridine side groups in a water / alcohol mixed solvent to prepare a perfluoro ion polymer solution or adding the perfluoro ion polymer to a conventional perfluorosulfonic acid polymer solution to prepare a perfluoro ion polymer composite solution, then adding a platinum-based catalyst to the perfluoro ion polymer solution or the perfluoro ion polymer composite solution, and ultrasonically obtaining a membrane electrode slurry;
[0071] (2) Spraying the membrane electrode slurry onto the hydrophobic treated gas diffusion layer to form a catalyst layer, and obtaining an electrode layer consisting of the gas diffusion layer and the catalyst layer after heat treatment. The obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with the fuel hydrogen and oxygen in the membrane electrode;
[0072] (3) Placing hydrogen electrodes and oxygen electrodes of appropriate sizes on the upper and lower sides of the proton exchange membrane, aligning them and fitting them perfectly, and performing a hot pressing process to produce a membrane electrode.
[0073] The gas diffusion layer (Gas Diffusion Layer) consists of a base layer and a microporous layer, wherein the base layer material is mostly porous carbon paper or carbon cloth, and the microporous layer is usually composed of conductive carbon black and a hydrophobic agent. The base layer is composed of a porous, non-woven carbon substrate with a macroporous structure. After the substrate is treated with PTFE hydrophobicity, a single or multi-layer microporous layer (MPL) is coated to form a porous structure with different pores.
[0074] Preferably, according to the present invention, the alcohol in the water / alcohol mixed solvent in step (1) is ethanol or isopropanol, and the volume ratio of water to alcohol is 1 to 2:8 to 9. Further preferably, the ultrasonic time is 30 to 200 min.
[0075] Preferably according to the present invention, the concentration of the perfluoro ion polymer in the perfluoro ion polymer solution or the perfluoro ion polymer composite solution in step (1) is 5 to 15 wt %.
[0076] According to the preferred embodiment of the present invention, the platinum loading of the catalyst layer in step (2) is 0.35-0.45 mg / cm 2 Further preferably, the heat treatment process in step (2) is 80-130° C. for 30-200 min.
[0077] According to the preferred embodiment of the present invention, the gas diffusion layer in step (2) is carbon paper treated with PTFE hydrophobicity. According to the preferred embodiment of the present invention, the proton exchange membrane in step (3) is the proton exchange membrane for fuel cells of the present invention or other conventional proton exchange membranes for fuel cells. Further preferably, the hot pressing process in step (3) is 0.1-5MPa, the hot pressing temperature is 80-140°C, and the duration is 30-150s.
[0078] In the present invention, when preparing a membrane electrode for a fuel cell, the chemical stability of the membrane electrode for a fuel cell can be regulated by adjusting the proportion of the perfluoroionic polymer according to the requirements of product performance, thereby regulating the length of its service life.
[0079] Beneficial effects:
[0080] The bipyridine group-containing long-life perfluorosulfonic acid resin and proton membrane of the present invention have the following advantages over previously proposed methods for resisting or slowing down free radical attacks (CN 102479956, CN101281967A, CN 108878993 A):
[0081] (1) The ultra-stable advantageous unit of perfluoropolymer - (CF2CF2)x - is retained, ensuring that the polymer can simultaneously meet the requirements of mechanical strength, thermal stability, and exchange capacity, and has high chemical stability and service life.
[0082] (2) Starting from the source of polymer, the present invention designs and synthesizes a type of perfluoroionic polymer with a functional bipyridine structural unit in the side chain, which can disperse or bind hydroxyl radicals through the conjugated structure of the bipyridine unit, thereby achieving the purpose of capturing or quenching free radicals, effectively weakening or slowing down the degradation of the polymer and extending the service life.
[0083] (3) By introducing the active bipyridine structural unit into the structure of the perfluoroion polymer, the grafting rate can be adjusted by adjusting the addition amount of the M group monomer reagent, the reaction temperature and time; thereby, the ion exchange capacity and chemical stability of the perfluoroion polymer can be adjusted according to product requirements.
[0084] (4) The perfluoro ion polymer obtained in the present invention is obtained by grafting a functional group having the function of quenching or capturing free radicals onto a polymer side chain through a chemical reaction, and can be evenly distributed in the ion membrane, thus protecting the ion membrane stably and for a long time against the attack of free radicals.
[0085] (5) The polymer synthesized in the present invention has both ion conduction and free radical corrosion resistance.
[0086] (6) The present invention provides a membrane electrode for a free radical resistant fuel cell, which can effectively increase the service life of the membrane electrode.
[0087] (7) The polymer and proton membrane prepared by the present invention were subjected to free radical decay test for 110 days ( Figure 1 , Figure 2 ), the ion exchange capacity (IEC) retention rate of the polymer and the ion conductivity retention rate of the proton membrane are both as high as over 90%, proving that the obtained polymer and the perfluorosulfonic acid proton membrane have a high ability to resist free radical attack and can effectively improve the service life of the perfluorosulfonic acid proton membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 The stability test results of the target product A2 described in Example 1;
[0089] Figure 2 The stability test results of the proton membrane obtained in Example 1;
[0090] Figure 3 This is the infrared characterization result diagram of the target product A2 described in Example 1. DETAILED DESCRIPTION
[0091] The present invention is described in detail below in conjunction with specific embodiments, which are only used to illustrate the present invention in detail and are not used to limit the scope of the present invention. The present invention is not limited to the following embodiments, and other combination schemes derived from the present invention all belong to the protection scope of this patent.
[0092] In the embodiments and comparative examples, the polymer and proton membrane adopt Fenton test to accelerate the oxidation target product, so as to achieve the purpose of investigating the chemical stability of the polymer and proton membrane. The chemical stability of the polymer and proton membrane is evaluated by testing the retention rate (RV%) of IEC of the polymer and proton membrane before and after the Fenton test.
[0093] The specific conditions of the Fenton experiment are: 20ppm Fe 2+ Ions are added to 30wt% H2O2 to prepare Fenton's reagent. Then the polymer is immersed in Fenton's reagent in a water bath at 80℃. After a certain period of immersion, the IEC of the polymer is tested to determine the chemical stability of the polymer. In order to ensure the concentration of ·OH free radicals, the Fenton's reagent needs to be replaced every 3 hours.
[0094] Titration of ion exchange capacity IEC of polymer and proton membrane: accurately weigh a certain weight of dry polymer resin, then treat it in deionized water at 80℃ for 1h, and use a 1M NaCl aqueous solution for ion exchange for more than 12h. Collect the exchanged solution, use phenolphthalein as an indicator, and titrate with 0.1M NaOH standard solution until the solution turns pink. The IEC value of the polymer can be calculated according to the following formula:
[0095] IEC=(V NaOH ×C NaOH ) / m
[0096] Where:
[0097] V NaOH ——Volume of NaOH solution consumed, ml
[0098] C NaOH ——Molar concentration of NaOH solution, mmol / ml
[0099] m——The mass of PFSA dry polymer resin, g.
[0100] Ion exchange capacity of polymer and proton membranes IEC retention rate:
[0101] RV%=(IEC1-IEC0) / IEC0
[0102] Wherein: IEC1 and IEC0 represent the IEC of the polymer before and after the Fenton test, respectively.
[0103] Proton membrane ion conductivity determination: The membrane resistance R was tested using the two-electrode method. The instrument used was the electrochemical workstation Autolab PGSTA302. The frequency range was 106Hz-10Hz. The formula was used to calculate
[0104] σ=L / RS to calculate conductivity;
[0105] Where:
[0106] L is the thickness of the membrane (cm), R is the resistance of the membrane (Ω), σ is the conductivity of the sample (S / cm), and S is the test area of the sample (cm 2 ).
[0107] Retention rate of proton membrane conductivity:
[0108] RV%=(σ1-σ0) / σ0
[0109] Where: σ1 and σ0 represent the ionic conductivity of the membrane before and after the Fenton experiment.
[0110] Thermal degradation temperature (defined as the temperature at which the polymer degrades by 5%): The test was conducted using a thermogravimetric analyzer, TAQ50 produced by Perkin Elmer, USA, with N2 atmosphere, a heating rate of 10° / min, and a temperature range of 50-800°C. The samples were dried at 60°C for 24 hours before testing.
[0111] Membrane electrode durability test:
[0112] The durability or chemical stability of the membrane electrode samples was evaluated at open circuit voltage (OCV) at 30% relative humidity (RH) and 90°C, with hydrogen and air gas flow rates of 3.43 slpm and 8.37 slpm, respectively. The OCV of each cell in the stack was monitored over time. When the OCV of any of the five cells in the stack reached 0.8 V or the H2Crosover was greater than 10 mA / cm 2 , end the test.
[0113] Example 1
[0114] A long-life perfluorosulfonic acid polymer containing bipyridine groups, a proton membrane and a preparation method thereof, and the specific implementation methods are as follows:
[0115] 4-amino-2,2'-bipyridine was selected as a reagent monomer providing the bipyridine group M, and reacted with a perfluorosulfonyl fluoride resin (m=1, n=2, number average molecular weight of 430,000, x value of 10) to prepare a long-life perfluorosulfonic acid polymer and a proton membrane. The specific experimental steps are as follows:
[0116] (1) After cleaning the 150mL reactor, add 35g of perfluorosulfonyl fluoride resin to 50mL of N,N-dimethylformamide, turn on the stirring device, heat to 60℃, and pre-swell for 60min. After evacuating and replacing with high-purity nitrogen three times, add 0.08g of 4-amino-2,2'-bipyridine. After it is completely dissolved, slowly heat to 80℃ for reaction. The molar ratio of perfluorosulfonyl fluoride resin to 4-amino-2,2'-bipyridine is about 1:5.3. After reacting at 80℃ under mechanical stirring for 20h, cool to room temperature (25℃), filter the product, wash it with ethanol and deionized water for several times to remove unreacted 4-amino-2,2'-bipyridine, and dry it to obtain the intermediate product, which is recorded as A1. The reaction process is as follows:
[0117]
[0118] (2) The polymer A1 obtained in step (1) was treated with 30 wt% sodium hydroxide and 25 wt% sulfuric acid at 80°C for 24 h to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) were converted into perfluorosulfonic acid groups (-SO3H). The product was washed with deionized water for multiple times and dried at 60°C for 18 h to obtain the target product, which was recorded as A2. The reaction process is as follows:
[0119]
[0120] The polymer A2 obtained in step (2) was dissolved in N,N-dihydrogen sulfoxide and subjected to ion exchange capacity (IEC) measurement. The IEC of the obtained target product A2 was 0.97 mmol / g. In the structure of the obtained target product A2, y / y+z=0.26 (i.e., grafting ratio).
[0121] The intermediate target product A2 was tested by infrared transmission spectrum, and the test results were as follows: Figure 3 As shown, after the reaction, 1467cm -1 The characteristic peak of -SO2F disappeared completely, and the CH bond, the NH bond of the connecting group and -SO3 - The characteristic peaks are at 1540cm -1 , 1660 and 1060cm -1 Nearby; infrared results proved that the target product A2 has been successfully synthesized.
[0122] The stability of the target product A2 was tested by Fenton test. Figure 1 As shown, after 110 days of free radical decay test, the ion exchange capacity (IEC) retention rate is as high as more than 90%, which proves that the obtained perfluoro ion polymer has a high ability to resist free radical attack and can effectively improve the service life of the perfluoro ion polymer.
[0123] (3) The polymer A2 obtained in step (2) is dissolved in N,N-dimethylformamide to prepare a 15 wt% polymer solution, and then the solution is coated on a clean and smooth quartz surface dish, pre-dried at 80° C., placed in an oven at 145° C. for 90 minutes, taken out and demolded, to prepare a long-life perfluorosulfonic acid proton membrane.
[0124] The ion conductivity of the proton exchange membrane in deionized water at 25°C is 80 mS / cm, and the conductivity described in the present invention is measured under this condition. The stability of the proton exchange membrane was tested by Fenton test, and the results are as follows: Figure 2 After 110 days of free radical decay test, the ion conductivity retention rate of the proton exchange membrane is as high as over 90%, which proves that the obtained proton exchange membrane has a high ability to resist free radical attack and can effectively improve the service life of the proton exchange membrane.
[0125] Example 2
[0126] A long-life perfluorosulfonic acid polymer containing bipyridine groups, a proton membrane and a preparation method thereof, the specific implementation methods are as follows:
[0127] 5-amino-2,2'-bipyridine was selected as a monomer reagent providing the M group to react with a perfluorosulfonyl fluoride resin (m=1, n=2, number average molecular weight of 450,000, x value of 10) to prepare the target proton membrane. The specific experimental steps are as follows:
[0128] (1) After cleaning a 150 mL reactor, add 50 mL of N, N-dimethylformamide, turn on the stirring device, evacuate and replace with high-purity nitrogen three times, add 0.10 g of 5-amino-2,2'-bipyridine, slowly heat to 80°C, and add 30 g of perfluorosulfonyl fluoride resin (the molar ratio of perfluorosulfonyl fluoride resin to 5-amino-2,2'-bipyridine is about 1:8) after it is completely dissolved. React at 80°C under mechanical stirring for 24 hours, then cool to room temperature, filter the product, wash it with ethanol and deionized water for several times to remove unreacted 5-amino-2,2'-bipyridine, and dry it to obtain an intermediate product, which is recorded as A3. The reaction process is shown below.
[0129]
[0130] (2) The polymer A3 obtained in step (1) is treated with 30 wt % sodium hydroxide and 25 wt % sulfuric acid to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) are converted into perfluorosulfonic acid groups (-SO3H). The product is washed with deionized water for multiple times and dried at 60° C. for 24 h to obtain the target product, which is recorded as A4. The reaction process is as follows:
[0131]
[0132] The ion exchange capacity (IEC) was measured and the IEC of the target product A4 was 1.06 mmol / g; in the structure, y / y+z=0.30.
[0133] (3) The target product A4 obtained in step (2) was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt% perfluoro ion polymer solution, and then the solution was coated on a clean and smooth quartz surface dish, pre-dried at 80° C., placed in an oven at 145° C. for 90 minutes, and removed from the mold to prepare a long-life perfluorosulfonic acid proton membrane. The ion conductivity of the obtained proton exchange membrane was 85 mS / cm.
[0134] Example 3
[0135] A long-life perfluoro ion polymer containing bipyridine groups, a proton membrane and a preparation method thereof, wherein 6-amino-2,2'-bipyridine is selected as a monomer reagent providing an M group and reacted with a perfluorosulfonyl fluoride resin (m=1, n=2, number average molecular weight of 480,000, x value of 12) to prepare a target proton membrane, and the specific experimental steps are as follows:
[0136] (1) After cleaning the 150mL reactor, add 50mL of N,N-dimethylacetamide, turn on the stirring device, evacuate and replace with high-purity nitrogen three times, add 0.10g of 6-amino-2,2'-bipyridine, slowly heat to 80°C, and add 40g of perfluorosulfonyl fluoride resin (the molar ratio of perfluorosulfonyl fluoride resin to 6-amino-2,2'-bipyridine is about 1:6.44) after it is completely dissolved. React at 80°C under mechanical stirring for 20h and then cool to room temperature. Filter the product and wash it with ethanol and deionized water several times to remove unreacted 6-amino-2,2'-bipyridine, and dry it to obtain the intermediate product, which is recorded as A5. The reaction process is as follows:
[0137]
[0138] (2) The polymer A5 obtained in step (1) is treated with 30 wt % sodium hydroxide and 25 wt % sulfuric acid to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) are converted into perfluorosulfonic acid groups (-SO3H). The product is washed with deionized water for multiple times and dried at 60° C. for 36 h to obtain the target product, which is recorded as A6. The reaction process is as follows:
[0139]
[0140] The ion exchange capacity (IEC) was measured and the IEC of the target product A6 was 1.16 mmol / g; in the structure, y / y+z=0.35.
[0141] (3) The intermediate product A6 obtained in step (2) was dissolved in a mixed solvent of ethanol / water (volume ratio = 9:1) to prepare a 15 wt% polymer solution, and then the solution was coated on a clean and smooth quartz surface dish, pre-dried at 80° C., placed in an oven at 145° C. for 90 minutes, and removed from the mold to prepare a long-life perfluorosulfonic acid proton membrane. The ion conductivity of the proton exchange membrane was 90 mS / cm.
[0142] Example 4
[0143] A composite proton membrane of a long-life perfluorosulfonic acid polymer containing a bipyridine group and a preparation method thereof, comprising the following steps:
[0144] (1) The target product A2 obtained in Example 1 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % perfluoro ion polymer solution A7.
[0145] (2) A perfluorosulfonic acid ionomer (having a number average molecular weight of 400,000, an ion exchange capacity of 0.95 mmol / g, a structural formula as shown below, and a being 10) having a structural formula as shown below was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % polymer solution A8.
[0146]
[0147] (3) Add the A7 solution to the A8 solution and mix them evenly by mechanical stirring, with the mass ratio of the two being 1:9. The resulting mixed solution is coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded, and a long-life perfluorosulfonic acid composite proton membrane is prepared.
[0148] After measurement, the ion exchange capacity (IEC) of the obtained composite proton exchange membrane is 0.96 mmol / g; and the ion conductivity of the composite proton exchange membrane is 75 mS / cm.
[0149] In the composite proton membrane, the mass content of the perfluoro ion polymer A2 is 10%.
[0150] Example 5
[0151] A composite proton membrane of a long-life perfluorosulfonic acid polymer containing a bipyridine group and a preparation method thereof, comprising the following steps:
[0152] (1) The target product A2 obtained in Example 1 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % polymer solution A9.
[0153] (2) A perfluorosulfonic acid ionomer, the structural formula of which is shown in Example 4, was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % polymer solution A10.
[0154] (3) Add the A9 solution to the A10 solution and mix them evenly by mechanical stirring, with the mass ratio of the two being 2:8. The resulting mixed solution is coated on a clean and smooth quartz surface dish, pre-dried at 80°C, and then placed in an oven at 145°C for 90 minutes, taken out and demolded, to prepare a bipyridyl-based long-life perfluorosulfonic acid composite proton membrane.
[0155] The IEC measurement showed that the ion exchange capacity (IEC) of the obtained composite proton exchange membrane was 0.97 mmol / g.
[0156] The ion conductivity of the composite proton exchange membrane is 82 mS / cm.
[0157] In the composite proton membrane, the mass content of the perfluoro ion polymer A2 is 20%.
[0158] Example 6
[0159] The preparation of a membrane electrode for a free radical resistant fuel cell comprises the following specific steps:
[0160] (1) The target product A2 in Example 1 was dissolved in a water / isopropanol (volume ratio of 2:8) mixed solvent to prepare a 5 wt% perfluoro ion polymer solution, and then 10 mL of the perfluoro ion polymer solution was added to a Pt / C catalyst, and ultrasonicated for 100 min to obtain a membrane electrode slurry, wherein the mass fraction of the perfluoro ion polymer in the obtained slurry was 5%;
[0161] (2) coating the perfluoro ion polymer solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 90 minutes, removing from the mold, and preparing a proton exchange membrane;
[0162] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130°C for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , an electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained, and the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode;
[0163] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the proton exchange membrane (3 cm×3 cm) in step (2), align them up and down and make sure they fit together perfectly, and then heat-press them using a press with a pressure of 0.8 MPa, a temperature of 140°C, and a duration of 60 seconds. Open the press, cool naturally, and then take out the resulting membrane electrode for fuel cells.
[0164] Example 7
[0165] The preparation of a composite membrane electrode for a free radical resistant fuel cell comprises the following specific steps:
[0166] (1) A8 in Example 4 was diluted in a mixed solvent of water / isopropanol (volume ratio of 2:8), and then the target product A2 in Example 1 was added to form a composite solution, wherein the total polymer concentration in the composite solution was 5 wt %, and the proportion of A2 in the total polymer was 30 wt %; then 10 mL of the mixed solution was added with a Pt / C catalyst, and ultrasonicated for 150 min to obtain a membrane electrode slurry, wherein the mass fraction of the polymer in the obtained slurry was 5%;
[0167] (2) coating the composite solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 90 minutes, taking out and demolding, thereby preparing a composite proton exchange membrane;
[0168] (3) The catalyst mixture of step (1) was sprayed onto the 2 cm×2 cm gas diffusion layer that had been hydrophobically treated using a spray gun to form a catalyst layer. After heat treatment at 130° C. for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , an electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained, and the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode;
[0169] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the composite proton exchange membrane (3 cm×3 cm) prepared in step (2), align them up and down and make sure they fit together perfectly, and then heat-press them using a press with a pressure of 0.8 MPa and a temperature of 140°C for 60 seconds. Open the press, cool naturally, and take out the resulting composite membrane electrode for fuel cells.
[0170] Comparative Example 1
[0171] The proton exchange membrane was prepared using unmodified perfluorosulfonic acid polymer as raw material. The perfluorosulfonic acid ion polymer (same as described in Example 4) was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20wt% polymer solution A8 without adding any additives. The obtained mixed solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, and removed from the mold to prepare a perfluorosulfonic acid proton membrane. The ion conductivity of the proton exchange membrane was 60mS / cm.
[0172] Comparative Example 2
[0173] The membrane electrode is prepared using unmodified perfluorosulfonic acid polymer as raw material, and the specific steps are as follows:
[0174] (1) The perfluorosulfonic acid polymer solution A8 of Example 4 was diluted in a mixed solvent of isopropanol / water (volume ratio of 8:2) to prepare a 5 wt% perfluorosulfonic acid polymer solution, and then 10 mL of the perfluorosulfonic acid polymer solution was added to a Pt / C catalyst, and ultrasonicated for 100 min to obtain a membrane electrode slurry, wherein the mass fraction of the unmodified perfluorosulfonic acid polymer in the obtained slurry was 5%;
[0175] (2) coating a 5 wt % perfluorosulfonic acid polymer solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 80 minutes, removing the solution from the mold, and preparing a perfluorosulfonic acid proton exchange membrane;
[0176] (3) The membrane electrode slurry of step (1) was sprayed onto the 2 cm×2 cm gas diffusion layer after hydrophobic treatment using a spray gun to form a catalyst layer. After heat treatment at 130° C. for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , an electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained, and the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode;
[0177] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the proton exchange membrane (3 cm×3 cm) in step (2), align them up and down and make sure they fit together perfectly, and then process them by hot pressing with a press. The press pressure is 0.8 MPa, the hot pressing temperature is 140°C, and the duration is 60 seconds. Open the press, and take out the obtained membrane electrode after natural cooling.
[0178] Comparative Example 3
[0179] A composite proton membrane for a fuel cell and a preparation method thereof, wherein 4-amino-2,2'-bipyridine is directly used as an additive for the proton exchange membrane without chemically grafting with a perfluoro ion polymer, and specifically comprises the following steps:
[0180] 4-amino-2,2'-bipyridine was directly added as an additive to the perfluorosulfonic acid polymer solution A8, and the mixture was uniformly mixed by mechanical stirring. The molar ratio of the perfluorosulfonic acid polymer to 4-amino-2,2'-bipyridine in the mixed solution was about 1:5.3. The obtained mixed solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded, and a proton exchange membrane was prepared.
[0181] After measurement, the ion exchange capacity (IEC) of the obtained composite proton exchange membrane is 0.90 mmol / g. The ion conductivity of the composite proton exchange membrane at room temperature (25° C.) is 55.5 mS / cm.
[0182] Comparative Example 4
[0183] A preparation method of a membrane electrode directly uses 4-amino-2,2'-bipyridine as an additive component of the membrane electrode, and the specific steps are as follows:
[0184] (1) A8 in Example 4 was diluted in a water / isopropanol (volume ratio of 2:8) mixed solvent to a concentration of 5 wt %, and then 4-amino-2,2'-bipyridine was added to prepare a perfluoro ion polymer composite solution, wherein the molar ratio of perfluorosulfonic acid polymer to 4-amino-2,2'-bipyridine in the composite solution was about 1:5.3, and then 10 mL of the composite solution was added with a Pt / C catalyst, and ultrasonicated for 150 min to obtain a membrane electrode slurry;
[0185] (2) coating the perfluoro ion polymer composite solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 90 minutes, taking out and demolding, thereby preparing a proton exchange membrane;
[0186] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130° C. for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , the obtained electrode layers are hydrogen electrode and oxygen electrode;
[0187] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the proton exchange membrane (3 cm×3 cm) in step (2), align them up and down and make sure they fit together perfectly, and then perform hot pressing on them with a press. The press pressure is 0.8 MPa, the hot pressing temperature is 140°C, and the duration is 60 seconds. Open the press, cool naturally, and then take out the prepared membrane electrode.
[0188] The perfluoro ion polymer, proton exchange membrane and membrane electrode prepared above were tested for performance, and the results are shown in Tables 1 to 3:
[0189] Table 1. Chemical stability test results of perfluoroionomers
[0190]
[0191] After the perfluoro ion polymer prepared by the present invention is tested for 200 hours by Fenton test, its IEC is all above 93%, and its thermal degradation temperature is all above 290°C. Compared with the unmodified perfluorosulfonic acid polymer, its IEC retention rate and thermal degradation temperature are significantly improved. This shows that the perfluoro ion polymer with bipyridine side groups prepared by the present invention has high chemical stability, weakens or slows down the degradation of the polymer, and has sufficient mechanical strength and thermal stability.
[0192] Table 2. Performance test results of proton exchange membrane
[0193]
[0194]
[0195] The proton exchange membrane prepared by the perfluoro ion polymer with bipyridine side groups of the present invention has an ion conductivity retention rate of more than 92% after being tested by the Fenton test for 200 hours, and the thermal degradation temperature of the proton exchange membrane is more than 300°C; the composite proton exchange membrane prepared by the perfluoro ion polymer with bipyridine side groups of the present invention has an ion conductivity retention rate of more than 92% after being tested by the Fenton test for 200 hours, and the thermal degradation temperature of the composite proton exchange membrane is more than 300°C; compared with the proton exchange membrane prepared by the perfluorosulfonic acid polymer without modification (Comparative Example 1), the chemical stability, mechanical strength and thermal stability of the proton exchange membrane of the present invention are significantly improved, and the service life of the proton exchange membrane is effectively extended.
[0196] Table 3. Performance test results of membrane electrode
[0197] Example 6 Example 7 Comparative Example 2 Comparative Example 4 Duration (h) 240 230 105 80
[0198] The membrane electrode prepared by the perfluoroionic polymer with bipyridine side groups of the present invention can last for more than 200 hours at open circuit voltage (OCV), 30% relative humidity (RH) and 90°C, while the membrane electrode prepared by the unmodified perfluorosulfonic acid polymer (Comparative Example 2) lasts only 105 hours. It shows that the durability of the membrane electrode prepared by the present invention has been effectively improved. Comparative Example 3 is to directly add 4-aminopyridine to the unmodified perfluorosulfonic acid polymer to prepare the proton exchange membrane. Since small molecules are easy to agglomerate and lose, and do not contain ionic groups, the compatibility is poor, which leads to a decrease in its mechanical properties and conductivity, but affects the service life.
Claims
1. A long-life proton exchange membrane with bipyridine side groups, characterized in that: The components of the proton membrane include a perfluoro ion polymer with bipyridine side groups, and the structure of the polymer is shown in formula (I): Wherein, the structure of formula (I) comprises an A unit and a B unit: the A unit is a bipyridine structural unit, which comprises a bipyridine group M and a perfluoroether structural unit, and the B unit comprises an ionic group -SO3H and a perfluoroether structural unit; In the structure of formula (I), m is an integer of 0-5, and n is an integer of 1-6; In the structure of formula (I), x is an integer of 1 to 30, (x+y) / (x+y+z)=0.10 to 0.80, y / (y+z)=0.20 to 0.70; The structure of the monomer reagent providing the bipyridine group M in the A unit is shown in formula (II): At least one of the R1 to R8 groups contains -NH2, and the other groups are electron-withdrawing groups or electron-donating groups, and the number of electron-withdrawing groups does not exceed 3.
2. The long-life proton exchange membrane with bipyridine side groups according to claim 1, characterized in that: m is an integer of 1 to 3, and n is an integer of 1 to 3; preferably, m is 1 and n is 2; Preferably, (x+y) / (x+y+z)=0.20-0.40, y / (y+z)=0.20-0.40; more preferably, y / y+z=0.26-0.35; Preferably, the number average molecular weight of the perfluoroionic polymer with bipyridyl side groups of formula (I) is 200,000 to 1,000,000, preferably 200,000 to 600,000, and more preferably 300,000 to 500,000.
3. The long-life proton exchange membrane with bipyridine side groups according to claim 1, characterized in that: The R1 to R8 groups are independently -NH2, -CH2NH2, -Ph, -PhNH2, -PhCOOH, -Cl, -O-CH3, -CH3, -H, -F, -Br, CH3CH2-, (CH3)2CH-, or (CH3)3C-. Preferably, the R1 to R5 are not all -NH2 at the same time; the number of -NH2 in R1 to R5 is at most 3. Preferably, R1 is -H, -Br, -Cl, -O-CH3 or -CH3; R2 is -H, -NH2, -Cl or -CH3; R3 is -H, -Br, -Ph or -CH3; R4 is -H, -Br, -Cl, -Ph or -CH3; R5 is -H, -Br, -NH2 or -CH3; R6 is -H, -Br, -Cl, -O-CH3 or -CH3; R7 is -H, -Br, -NH2, -NO2 or -CH3; R8 is -H, -Br, -NH2 or -CH3. Further preferably, R1 is -H, -Br or -CH3; R2 is -NH2 or -CH3; R3 is -H, -Ph or -CH3; R4 is -H, -Ph or -CH3; R5 is -NH2 or -CH3; R6 is -H, -Br or -CH3; R7 is -H, -NH2 or -NO2; R8 is -H, -NH2 or -CH3. Preferably, R8 is -NH2, and R1, R2, R3, R4, R5, R6, and R7 are H. Preferably, R1 is -NH2, and R2, R3, R4, R5, R6, R7, and R8 are H. Preferably, R2 is -NH2, and R1, R3, R4, R5, R6, R7, and R8 are H.
4. The long-life proton exchange membrane with bipyridine side groups according to any one of claims 1 to 3, characterized in that: The synthesis method of the perfluoroion polymer comprises the following steps: (1) a perfluorosulfonyl fluoride resin as shown in the structure of formula (III) is subjected to a one-step grafting reaction with a monomer reagent providing a bipyridine group M in an organic solvent to synthesize an intermediate product with a bipyridine side group as shown in the structure of formula (IV); The reaction process is shown in formula (1-1): (2) The intermediate product obtained in step (1) is treated with alkali and acid to complete ion exchange, and the unreacted sulfonyl fluoride group (-SO2F) is converted into a sulfonic acid group (-SO3H). After washing and drying, a perfluoroionic polymer with bipyridine side groups as shown in the structure of formula (I) is obtained. The reaction process is shown in formula (1-2):
5. The long-life proton exchange membrane with bipyridine side groups according to any one of claims 1 to 3, characterized in that: The ion exchange capacity of the proton exchange membrane is 0.9-1.5 mmol / g, the ion conductivity is 50-200 mS / cm, the thermal degradation temperature is 300-325°C, and after 200 hours of Fenton test, the ion exchange capacity retention rate and the ion conductivity retention rate are both above 93%. Preferably, the ion conductivity of the proton exchange membrane is 80-90 mS / cm. Preferably, the thickness of the proton exchange membrane is 10-200 μm.
6. The method for preparing a long-life proton exchange membrane according to any one of claims 1 to 5, characterized in that: The perfluoro ion polymer with bipyridine side groups is dissolved in an organic solvent to obtain a perfluoro ion polymer solution, and then a perfluorosulfonic acid proton exchange membrane is directly prepared by a solution casting method; Alternatively, the above-mentioned perfluoro ion polymer with bipyridine side groups is added as a free radical quencher into a conventional perfluorosulfonic acid resin solution to obtain a perfluoro ion polymer composite solution, and the composite proton membrane is prepared by a solution casting method.
7. The preparation method according to claim 6, characterized in that: The mass fraction of the perfluoro ion polymer solution is 5 to 35 wt %, more preferably 10 to 25 wt %.
8. The preparation method according to claim 6, characterized in that: The organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, ethanol / water mixed solvent, isopropanol / water mixed solvent, dimethyl sulfoxide or ethyl acetate. Preferably, the volume ratio of ethanol to water in the ethanol / water mixed solvent is 8-9:1-2; the volume ratio of isopropanol to water in the isopropanol / water mixed solvent is 8-9:1-2.
9. The preparation method according to claim 6, characterized in that: The mass proportion of the perfluoro ion polymer with bipyridine side groups in the composite proton membrane is greater than or equal to 5%, and more preferably greater than or equal to 10%. Preferably, the mass fraction of the perfluoro ion polymer composite solution is 5 to 30 wt %.
10. The preparation method according to claim 6, characterized in that: The solution casting method comprises the following steps: coating a perfluoro ion polymer solution or a perfluoro ion polymer composite solution on a quartz surface dish, pre-drying at 80-90° C., drying at 140-150° C. for 90-100 minutes, and removing the solution from the mold.
Citation Information
Patent Citations
Oxidation resistance degradation composite roton switching membrana for fuel cell as well as preparation thereof
CN101281967A
Method for improving chemical stability of proton exchange membrane
CN102479956A
Method for reducing electrochemical degradation of proton exchange membrane
CN108878993A